SELECTION OF POTATO PARENTAL LINES WITH COMPLEX RESISTANCES TO POTATO PATHOGENS AND PESTS - Flis, Bogdan (Plant Breeding and Seed Science, 2017)
The efficiency of breeding new potato cultivars may be increased by pre-breeding that is by developing parental lines, which have new traits, not present in the genetic pool available for breeders or have new combinations of genes, or have improved level of economically important traits. The use of parental lines in commercial breeding programs is expected to ensure the biological progress in the newly created cultivars of potato. At the beginning, the development of parental lines in Młochów Research Center of Plant Breeding and Acclimatization Institute – Nation-al Research Institute (IHAR-PIB) was focused on resistance to viruses and later on resistance to late blight and other pathogens. The procedures of selecting resistant parental lines are described. These procedures were initially based on purely phenotypic tests for resistance, which lately were supplemented with marker assisted selection (MAS) apply-ing molecular markers linked with some resistance genes.